Schaum's Outline of Theory and Problems of International Economics / Third Edition - Salvatore Dominick (Mcgraw Hill, Inc, 1990)
Covers all course fundamentals and supplements any class text - Teaches effective problem-solving techniques - 735 solved problems with complete solutions - Includes hundreds of additional problems with answers. Introduction, The Pure Theory of International Trade: Supply, The Pure Theory of International Trade: Demand and Supply, The Heckscher-Ohlin Theory and Extensions, Dynamic Factors in International Trade: Growth and Development, Trade Restrictions: Tariffs and Other Commercial Policies, The Foreign Exchange Markets, The Balance of Payments, Adjustments in the Balance of Payments: Automatic, Adjustment Policies: Open Economy Macroeconomics, The Monetary Approach to the Balance of Payments and Flexible Versus Fixed Exchange Rates, The International Monetary System: Past and Present, Index.